Model Penguatan Perkembangan Sosial dan Emosional Anak Melalui Pembelajaran Kolaboratif dan Empatik di Sekolah Dasar - Apriyanto, Sutrisno Condro; Restian, Arina; Makhali, Makhali; Devi Prastika Putri, Sinta (J-SES : Journal of Science, Education and Studies, 2025)
Elementary education currently tends to be dominated by cognitive achievement orientation, often neglecting students' social and emotional development. This imbalance contributes to character degradation phenomena, such as increasing bullying cases and a lack of tolerance among peers. This study aims to formulate a conceptual model for strengthening social-emotional development through the integration of collaborative and empathic learning. The method used is library research with content analysis techniques on developmental psychology literature, constructivist learning theories, and relevant curriculum documents. The results indicate that while collaborative learning provides the structure for interaction, it requires an empathic charge to ensure such interaction is meaningful. The synthesis of these two approaches produces a new learning model that modifies conventional cooperative syntax by inserting emotional interventions, such as "empathy contracts" and "emotional reflection." This model operates on the principles of positive interdependence and perspective-taking, transforming group dynamics from merely transactional to relational. This model is recommended as an effective pedagogical strategy for teachers to enhance students' emotional intelligence and social skills simultaneously with academic learning.